Evaluation of malaria microscopy diagnostic performance at the public health center on the border of Indonesia timor-leste - Kartini Lidia; Elisabeth Levina Sari Setianingrum; Magdarita Riwu; Christina Olly Lada; Hayani Anastasi (Wolters Kluwer Medknow Publications, 2024)
Accurate diagnosis is a key strategy for controlling and preventing malaria. Regular evaluation of the performance of malaria microscopy diagnosis is essential to ensure its high quality. This study aims to assess the accuracy of malaria microscopy at selected public health facilities on the border of Indonesia and Timor-Leste. The design of this research is observational with a cross-sectional approach, conducted at five public health centers located on the Indonesia Timor-Leste border from July to September 2022. Stained slides were collected from patients with a fever (≥37°C). These stained slides were then examined for malaria diagnosis. The results revealed that all five public health centers showed perfect or nearly perfect agreement with the reference microscopist regarding malaria detection by microscopy (κ =0.9-1). To maintain the high quality of malaria microscopy diagnosis, it is imperative to conduct regular training, monitoring, and evaluation.